A hospitalist's role in preventing patient falls. Issue 1 (31st March 2020) - Keuseman, Rachel; Miller, Donna
ABSTRACT: Despite decades of fall prevention efforts, patient falls remain a common cause of harm in hospitalized older adults. While fall prevention strategies have been historically championed by nurses, hospitalist physicians, nurse practitioners, and physician assistants play a vital role in the multidisciplinary care team in ensuring the safety of our patients. Multiple fall risk assessment tools exist, but no one tool has demonstrated excellence in predicting patient falls in the hospital. Any fall risk assessment tool should be complemented by a clinician's individualized evaluation of patient-specific, situational, and environmental risk factors. A particular emphasis on medication review is critical, as numerous medication classes can increase the risk of falls, and medications are a potentially modifiable risk factor. Multiple studies of individual and multicomponent nursing-based interventions have failed to demonstrate success in reducing falls or fall injuries. Promising strategies for fall prevention include tailoring interventions to patient risk factors and individualized patient education. In addition to nursing-based interventions, the hospitalist's role in fall prevention is to (1) identify and address potentially modifiable risk factors, (2) reinforce individualized education to patients, and (3) advise behavior choices that promote safe mobility. If a patient does sustain a fall, the hospitalist should partner with the multidisciplinary care team in post fall care to assess for injury, evaluate underlying causes of the fall, and determine plans for secondary prevention.